2012
DOI: 10.1007/s11665-011-0115-x
|View full text |Cite
|
Sign up to set email alerts
|

On the Early Stage Isothermal Oxidation of APS CoNiCrAlY Coatings

Abstract: The aim of this study is to analyze the evolution of microstructural and room temperature mechanical properties of air plasma sprayed (APS) CoNiCrAlY coatings before and after early stage high-temperature oxidation. To this purpose, selected samples were isothermally heat treated at 1110°C for different durations. Phase analysis and oxide scale characterization were performed using x-ray diffraction. Morphological and microstructural features of as-sprayed and oxidized CoNiCrAlY coatings were analyzed by scann… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 28 publications
1
15
0
Order By: Relevance
“…Operation in vacuum additionally prevents deleterious oxidation of the sample or the indenter tip [12,15,16]. Nanoindentation has been applied to superalloy materials [18,19] and their bond coats [20][21][22][23] with high-temperature nanoindentation recorded on CMSX-4 up to 400 • C [7] and René N4 up to 800 • C [24]. However, both works on high-temperature nanoindentation note the experimental difficulties -particular in the measurement of Young's modulus -due to creep during nanoindentation.…”
Section: Introductionmentioning
confidence: 99%
“…Operation in vacuum additionally prevents deleterious oxidation of the sample or the indenter tip [12,15,16]. Nanoindentation has been applied to superalloy materials [18,19] and their bond coats [20][21][22][23] with high-temperature nanoindentation recorded on CMSX-4 up to 400 • C [7] and René N4 up to 800 • C [24]. However, both works on high-temperature nanoindentation note the experimental difficulties -particular in the measurement of Young's modulus -due to creep during nanoindentation.…”
Section: Introductionmentioning
confidence: 99%
“…It is reported that the observed difference between the Young's modulus of TGO (preferably Al 2 O 3 ) and the bulk Al 2 O 3 is due to the presence of fine microcracks in TGO[19]. It is also reported that the Young's modulus of CoNiCrAlY is increased from 134-154 GPa to 202 -216 GPa due to thermal aging at 1100 °C for 24 h which further increases with increase in time[36]. Hence, the Young's modulus ranging from 174 to 193 GPa is contributed by the presence of CoNiCrAlY phase.…”
mentioning
confidence: 97%
“…In other words, the presence of Re in the microstructure is useful to promote the formation of a protective, well adherent, dense and quasi continuous Al2O3 layer at metal surface, so that the formation of mixed oxide scales is reduced at lower extent as well as the internal oxidation occurring at splat boundaries. Therefore, the β phase depletion and the oxidation rate of MCrAlYRe coatings are lower with respect to the conventional MCrAlY ones [6]. The addition of Re influences the morphology and the amount of the phases into the coating.…”
Section: Resultsmentioning
confidence: 98%
“…In this context, metal coatings can be successfully adopted to cover turbine components in order to improve their environmental resistance, without compromising their structural stability and mechanical strength [3][4][5]. Among them, the well-known MCrAlY (Me = Ni, Co or Ni/Co) coatings can be used as overlay coatings or in conjunction with an upper ceramic TBC [6,7].…”
Section: Introductionmentioning
confidence: 99%